Constitutional legislation in Iraq (1968_1979) (Journal of the College of Basic Education, 2023)
The constitutional legislation in the Arab world is almost similar to a great extent. Every Arab country that gained independence took from the constitutions of the countries that preceded it, and Iraq, for example but not limited to, developed several temporary constitutions that were similar in their provisions and legal articles since the fall of the monarchy in 1958 until the advent of the party The (dissolved) Baath of power in 1968, or what characterizes this period until 1970, we see that the legal legislation was limited to some extent by the decisions of the (dissolved) Revolutionary Command Council, which is the supreme authority in the country